(De)formados pela pele: a escola-periférica e a escola-excepcional fragmentada como (re)produtoras de desigualdades - Basílio, Ana Carolina Paula (2020)
The present work problematizes the “public school crisis” narrative in the light of notions of peripheral school, exceptional school and fractal school. Based in participatory action research, it was followed the routine of two state schools, located in the periphery and the central region of the city of Sorocaba, state of São Paulo. Along the research and the daily sharing with the students, it was identified that their bodily marks: race/ color, social class, gender, geographic location, family relationships etc., are fundamental to the analysis of school performances, and that in the process of social production of urban space, markedly fragmented and racialized, state schools “shatter” themselves, keeping within them not only classist but racial differences. The discussion about the fragmentation of the state schools, in a racial perspective, opened wide that the “crisis of the public school” has, historically, a color and an address, affecting mostly the peripheral school – black and in the periphery.